Immune mediated neuropathy following checkpoint immunotherapy. (November 2017) - Gu, Yufan; Menzies, Alexander M.; Long, Georgina V.; Fernando, S.L.; Herkes, G.
Highlights: Neuropathies are rare but potentially severe complications of checkpoint immunotherapy. Neurophysiology can show an axonal or demyelinating pattern. Cerebrospinal fluid often shows a lymphocytic pleocytosis. Immunotherapy varies, but should include corticosteroid therapy. Abstract: Checkpoint immunotherapy has revolutionised cancer therapy and is now standard treatment for many malignancies including metastatic melanoma. Acute inflammatory neuropathies, often labelled as Guillain-Barre syndrome, are an uncommon but potentially severe complication of checkpoint immunotherapy with individual cases described but never characterised as a group. We describe a case of acute sensorimotor and autonomic neuropathy following a single dose of combination ipilimumab and nivolumab for metastatic melanoma. A literature search was performed, identifying 14 other cases of acute neuropathy following checkpoint immunotherapy, with the clinical, electrophysiological and laboratory features summarised. Most cases described an acute sensorimotor neuropathy (92%) with hyporeflexia (92%) that could occur from induction up till many weeks after the final dose of therapy. In contrast to Guillain-Barre syndrome, the cerebrospinal fluid (CSF) analysis often shows a lymphocytic picture (50%) and the electrophysiology showed an axonal pattern (55%). Treatment was variable and often in combination. 11 cases received steroid therapy with only 1 death within this group, whereas of the 4 patients who did not receive steroid therapy there were 3 deaths. In conclusion checkpoint immunotherapy – induced acute neuropathies are distinct from and progress differently to Guillain-Barre syndrome. As with other immunotherapy related adverse events corticosteroid therapy should be initiated in addition to usual therapy.